A cross-sectional analysis of TikTok autism spectrum disorder content quality - Emma Brown; Faith Kuzmiak; Aakanksha Singh; Varun Monga; Theodore Bell; Jessica Nolan; Melissa Schlenker; Joan Moore; Rahul Kashyap (Elsevier, 2024)
Background: In the current digital age, individuals often look to the widely used social media application "TikTok" to obtain information about autism spectrum disorder (ASD). Despite this, no studies have evaluated the quality of information available about ASD on the app. Our aim was to investigate the understandability, actionability, and usefulness of TikTok videos about ASD. Methods: To evaluate video quality, 100 videos tagged with "autism spectrum disorder" were obtained from TikTok between June 19th-21st, 2023. Videos were included if they pertained to ASD and excluded if they were not in English, unrelated to ASD, or duplicates. Two systems were used to assess the videos. The Patient Education Materials Assessment Tool for Audio- Visual Materials (PEMAT-A/V) was used to obtain percentage scores for video understandability and actionability. The videos were also sorted into one of three categories: useful, personal experience, or misleading (UPM). The assignment was based on if they contained factual information, anecdotal personal experiences, or incorrect information, respectively. Results: Of the 100 videos analyzed, 24 % were classified as useful; 36 % as personal experience; and 40 % as misleading. They had a mean PEMAT-A/V understandability score of 60.1 % (SD=14.5, range=31.0-91.7 %) and a median PEMAT-A/V actionability score of 0 % (IQR=0-0, range=0-100 %). The breakdown of topics discussed in the videos were as follows: 62 % of videos discussed the diagnosis/symptoms of ASD, 17 % pertained to disorder management, 7 % gave an overview of the disorder as a whole, 2 % discussed the cause of ASD, and 7 % contained information classified as "other". The majority of the videos were made by non-HCPs (86 %), while the remaining videos were made by HCPs (14 %). HCPs uploaded a significantly higher percentage of useful content (50 %) than non-HCPs (20 %, p = 0.034). HCPs also uploaded a significantly higher percentage of Diagnosis/Symptoms content (85.7 %) than non-HCPs (62 %, p = 0.015). Conclusion: TikTok content about ASD is of unsatisfactory quality. Overall, videos are of moderate understandability, very low actionability, and are often misleading. Individuals should exercise caution when browsing the app for information about ASD, and HCPs should be aware that patients are likely to have been exposed to confusing or misleading information.